Anteseden Niat Beli pada Iklan Instagram untuk Produk Fashion dan Kecantikan - Calvin Christianto (Universitas Katolik Parahyangan, 2023)
This study aims to determine the relationship between Informativeness, Credibility, Flow Experience, Perceived Value, and Advertisement Value on Purchase Intention on Instagram ads for fashion and beauty products. The sample consisted of 250 people who lived in Jakarta and had seen advertisements for fashion and beauty products on Instagram. Respondents were active users of Instagram for the last three months, aged 18-44 years, and were interested in purchasing fashion and beauty products. The data that came from this study is cross-sectional data, where the data is obtained within a predetermined time and period. The results of this study explain that Informativeness and Credibility positively affect Flow Experience and Advertisement Value. Meanwhile, although the Flow Experience variable positively affects Perceived Value, the two variables do not positively affect Purchase Intention. Only the Advertisement Value variable has a positive effect on Purchase intention.